Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/2016jb012858
|View full text |Cite
|
Sign up to set email alerts
|

Fault geometry inversion and slip distribution of the 2010 Mw 7.2 El Mayor‐Cucapah earthquake from geodetic data

Abstract: The 4 April 2010 Mw 7.2 El Mayor‐Cucapah (EMC) earthquake in Baja, California, and Sonora, Mexico, had primarily right‐lateral strike‐slip motion and a minor normal‐slip component. The surface rupture extended about 120 km in a NW‐SE direction, west of the Cerro Prieto fault. Here we use geodetic measurements including near‐ to far‐field GPS, interferometric synthetic aperture radar (InSAR), and subpixel offset measurements of radar and optical images to characterize the fault slip during the EMC event. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…We suggest that the earthquake's northward propagation onto numerous faults was the result of static stress changes imposed by the earlier stages of the rupture although dynamic stressing may also have played a role (34). Using only the fault slip from The Humps and Hundalee faults in the south, we calculate positive static stress changes (29) over much of the Upper Kowhai Fault and Jordan Thrust up to ~0.75 MPa (Figure 7).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We suggest that the earthquake's northward propagation onto numerous faults was the result of static stress changes imposed by the earlier stages of the rupture although dynamic stressing may also have played a role (34). Using only the fault slip from The Humps and Hundalee faults in the south, we calculate positive static stress changes (29) over much of the Upper Kowhai Fault and Jordan Thrust up to ~0.75 MPa (Figure 7).…”
Section: Discussionmentioning
confidence: 95%
“…This gap coincides with a change from more reverse faulting in the south to predominantly strike slip in the north and is more than double the distance usually assumed as the limit for halting a fault rupture in standard seismic hazard models. The 2010 Mw 7.2 El Mayor-Cucapah in northern Mexico ruptured across a 10 km step-over in the surface faults, but gradients in optical pixel offsets and InSAR data indicated that slip continued at depth (7,34). During the Kaik ura earthquake, slip along the interface could also act as a linking structure at depth.…”
Section: Discussionmentioning
confidence: 99%
“…Other works before ours presented estimates of the slip distribution for the El Mayor‐Cucapah event (Fialko et al, ; Gonzalez‐Ortega et al, ; Huang et al, ; S. Wei et al, ). The data sets used to constraint the final slip include teleseismic waveforms, InSAR points, GPS measurements, SPOT images, and/or various combinations of these.…”
Section: Discussionmentioning
confidence: 99%
“…S. Wei et al () also showed that rupture propagated bilaterally, toward the NW and SE. Models that incorporate geodetic data represent the interface geometry as a concatenation of four to eight faults and with maximum slip between 5 and 6 m (Fialko et al, ; Gonzalez‐Ortega et al, ; Huang et al, ; S. Wei et al, ). They also show that the majority of slip occurred in the northern region of the fault interface.…”
Section: Introductionmentioning
confidence: 99%
“…For the range of regularization values, the lidar-optical-InSAR inversion resolves a greater maximum slip than does the optical-InSAR inversion. Huang et al (2017) observed that the regularization affects the depth profile of slip for the 2010 M7.2 El Mayor-Cucapah earthquake. The moment release migrates from the Hinagu to Futagawa Fault with increasing regularization (Figure 4c).…”
Section: Regularizationmentioning
confidence: 98%